Lineage origin and transcriptional control of autoantigen-specific T-regulatory type 1 cells - Angelats, Edgar; Santamaria, Pere (Frontiers in Immunology, 2023)
T Regulatory type-1 (TR1) cells represent an immunosuppressive T cell subset, discovered over 25 years ago, that produces high levels of interleukin-10 (IL-10) but, unlike its FoxP3+ T regulatory (Treg) cell counterpart, does not express FoxP3 or CD25. Experimental evidence generated over the last few years has exposed a promising role for TR1 cells as targets of therapeutic intervention in immune-mediated diseases. The discovery of cell surface markers capable of distinguishing these cells from related T cell types and the application of next generation sequencing techniques to defining their transcriptional make-up have enabled a more accurate description of this T cell population. However, the developmental biology of TR1 cells has long remained elusive, in particular the identity of the cell type(s) giving rise to bona fide TR1 cells in vivo. Here, we review the fundamental phenotypic, transcriptional and functional properties of this T cell subset, and summarize recent lines of evidence shedding light into its ontogeny.